A Study on Romantic Attachment Style and Parasocial Relationships - Asees Singh Sibia; Maya Jaypal; Saanika Sagar; Samantha Ann Thomas; Sanjana Sai Prasad; Dr. Prof. Blessy Ann Varghese (International Journal of Indian Psychȯlogy, 2022)
The increasing popularity of Over-the-top (OTT) media platforms and various forms of media has led to people talking and relating to media characters and figures. It, therefore, is interesting and also the aim of the study to understand if there is a relationship between romantic attachment styles, and one’s parasocial relationships. The study was conducted on a sample of 170. The method for analysis used was correlational analysis. The correlation between the two variables is also interesting as the sample only consisted of young Indian adults in the age group of 18-25. Previous studies were only done either on undergraduate students, or on adolescents. Another gap that the primary investigators noticed was that the previous studies used only celebrities to study Parasocial relationship. Hence, the researchers wanted to fill this gap. The scales used for this study were (a) Adult Attachment Scale (Collins & Read, 1990), and Multiple Parasocial Relationship Scale (Tukachinsky, 2010). It was hypothesized that there would be no significant correlation between romantic attachment style, and parasocial relationships; and there would be a significant correlation between romantic attachment styles (Secure, Preoccupied, Dismissing, and Fearful) and Parasocial Relationship respectively. It was found that there is no significant correlation between romantic attachment styles, and parasocial relationship. However, there may be other factors that must have contributed to this result, and conclusion.